APPLICATION OF ARTIFICIAL INTELLIGENCE COMPONENTS IN THE STUDY OF COMPUTER SCIENCE BY COLLEGE STUDENTS - Bazhan , Stanislav (Collection of scientific papers «ΛΌГOΣ», 2023)
Artificial intelligence (AI) is playing an increasingly important role in the modern world. The use of AI in education provides an opportunity to improve the quality of education and stimulate students. Computer science students need to be regularly exposed to modern trends. This will allow students to become specialists in their chosen professional field. Acquiring professional competences and practical skills is an important component for students.